Computational modelling of small motorcycle crashes and experimental validation - Tan, Kean Sheng (2016)
Researches in motorcycle crash simulations have been largely focused on the large motorcycles that are commonly found on the roads in developed nations, whereas for the small motorcycles that are used as daily transport in developing nations, the development is relatively far lacking. The present study was thus set out to create and validate a finite element model of a small motorcycle with fully deformable capability for simulating frontal crashes, and to establish guidelines for the entire development process. The Malaysian national motorcycle, Modenas Kriss 110, was selected as the reference motorcycle and the model was developed in LS-DYNA environment. The front wheel and fork which often experience severe and highly dynamic deformations in frontal crashes were modelled to be fully deformable for capturing detail deformation mechanisms and also interactions involved. The models of these crucial subassemblies were validated separately against experimental data. The overall validity and sensitivity of the models were also assessed using factorial experiment approach.The validated front subassemblies were then assembled together with other parts to form the full motorcycle model. A specially designed apparatus and the associated measuring technique were developed to determine the location of centre of gravity and mass moment of inertia of the actual motorcycle. These inertial properties were incorporated in the full motorcycle model. The full motorcycle model was validated against an actual laboratory-based full motorcycle impact test. The global behaviour of the motorcycle and the major deformations sustained particularly by the front wheel and fork were compared. Time histories of motorcycle kinematics were validated against the test data using Roadside Safety Verification and Validation Program(RSVVP). The computed values of the metrics Sprague-Geers MPC and ANOVA are all met the acceptance criteria: 17.6%(magnitude), 16.5% (phase), 24.2% (comprehensive), 0.9% (average) and 21.6% (standard deviation) for the horizontal acceleration; -11%, 22.7%, 25.2%, 0.8% and 19.8% for the corresponding metrics for the vertical acceleration. It is thus concluded that the validated motorcycle model was successfully developed. Detail modelling aspects in developing the models including major numerical instabilities encountered and proposed resolutions, and also limitations and discrepancies exhibited by the models were discussed. The robustness of the model was demonstrated by its capability in simulating severe deformations and the geometric failure of the rim. A guideline to effectively and systematically develop a high fidelity finite element model of a small motorcycle for use in simulating frontal collision of a motorcycle was established.